Radiofrequency polarization effects in zero-field electron paramagnetic resonance. - Rodgers, C; Wedge, C; Norman, SA; Kukura, P; Nelson, K; Baker, N; Maeda, K; Henbest, K; Hore, P; Timmel, C (2009)
Optically detected zero-field electron paramagnetic resonance spectroscopy is used to show that weak linearly and circularly polarized radiofrequency magnetic fields affect the recombination reactions of spin-correlated radical pairs to different extents; the spectra are shown to be consistent with the radical pair mechanism.